Synthesis, Characterizations and Antimicrobial Activity of Metal Complexes of 2-(2-Furanylmethylaminocarbonyl)benzoic Acid. Issue 1 (2011) - Patel, R. H.; Hiran, B. L.
Abstract : The ligand, 2-(2-furanylmethylaminocarbonyl)benzoic acid (FMBA) and it's transition metal complexes have been synthesized and characterized by elemental analysis, spectral studies, magnetic moments and thermal studies. The antifungal activity of all the samples was monitored against common fungi.